2008
DOI: 10.1007/s10620-008-0522-5
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Helicobacter pylori in Paraffin-Embedded Specimens from Patients with Chronic Liver Diseases, Using the Amplification Method

Abstract: Helicobacter DNA has been detected in the liver specimens of patients with various hepato-biliary diseases. The aim of this study was to investigate the presence of H. pylori DNA in the liver tissue of Iranian patients with chronic liver diseases (CLD). Genomic DNA was extracted from the paraffin sections of 46 liver biopsies of patients with CLD and 13 from patients with metastatic adenocarcinoma as a control group. Polymerase chain reaction (PCR) analysis was carried out using primers for H. pylori 16S rRNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 29 publications
3
48
0
2
Order By: Relevance
“…on liver samples of a patient with NASH has been initially reported (9) . This finding was validated by another study, in which the 16S recombinant RNA was found in 5/11 liver samples of NAFLD patients compared with 2/13 controls (17) . However, it remains unclear whether Hp in these specimens is an incidental finding or it has the potential to affect the natural course of NAFLD.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…on liver samples of a patient with NASH has been initially reported (9) . This finding was validated by another study, in which the 16S recombinant RNA was found in 5/11 liver samples of NAFLD patients compared with 2/13 controls (17) . However, it remains unclear whether Hp in these specimens is an incidental finding or it has the potential to affect the natural course of NAFLD.…”
Section: Discussionsupporting
confidence: 60%
“…There are only limited clinical data regarding the association between Hp infection and NAFLD (9,17,19,28) . The presence of 16S recombinant RNA of Hp spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, in the last years, H. pylori infection has also been associated with some extradigestive diseases, such as iron-deficiency anemia [20], idiopathic thrombocytopenic purpura [21,22], cardiovascular diseases [23,24], hepatobiliary diseases [25,26], and diabetes mellitus [27], among others.…”
Section: General Characteristicsmentioning
confidence: 99%
“…In the first case, H. pylori infection is responsible for the development of chronic gastritis, peptic ulcers, mucosa associated lymphoid tissue (MALT lymphoma) and gastric adenocarcinoma (Ahmed & Sechi, 2005). Regarding to extradigestive diseases, H. pylori infection has been associated with iron-deficiency anemia (Capurso et al, 2001), idiopathic thrombocytopenic purpura (Pellicano et al, 2009;Arnold et al, 2009), cardiovascular diseases , hepatobiliary diseases (Isaeva et al, 2009;Pirouz et al, 2009) and amongst others. Especially with regards to gastric cancer, the interest in H. pylori as a cause of this illness began after the pioneering discoveries of Marshall and Warren.…”
Section: Introductionmentioning
confidence: 99%